2015
DOI: 10.1007/s10955-015-1211-3
|View full text |Cite
|
Sign up to set email alerts
|

Examples of DLR States Which are Not Weak Limits of Finite Volume Gibbs Measures with Deterministic Boundary Conditions

Abstract: We review what is known about the structure of the set of weak limiting states of the Ising and Potts models at low enough temperature, and in particular we prove that the mixture 1 2 (µ ± + µ ∓ ) of two reflection-symmetric Dobrushin states of the 3-dimensional Ising model at low enough temperature is a Gibbs state which is not a limit of finitevolume measures with deterministic boundary conditions. Finally we point out what the issues are in order to extend the analysis to the Potts model, and give a few con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
9
0
3
Order By: Relevance
“…This is the case in four or more spatial dimensions, where bounded transverse fluctuations of an interface allow non-translationally invariant extremal equilibrium states (satisfying cluster decomposition) to exist. 8 Such states may be viewed as the limit of finite volume equilibrium states in which one fixes degrees of freedom on the boundary of the volume in a non-uniform manner which pins the interface location on the boundary and selects the desired volume fraction x [29]. But in three or fewer spatial dimensions, which the following discussion assumes, the transverse fluctuations in interface position diverge as V → ∞.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…This is the case in four or more spatial dimensions, where bounded transverse fluctuations of an interface allow non-translationally invariant extremal equilibrium states (satisfying cluster decomposition) to exist. 8 Such states may be viewed as the limit of finite volume equilibrium states in which one fixes degrees of freedom on the boundary of the volume in a non-uniform manner which pins the interface location on the boundary and selects the desired volume fraction x [29]. But in three or fewer spatial dimensions, which the following discussion assumes, the transverse fluctuations in interface position diverge as V → ∞.…”
Section: )mentioning
confidence: 99%
“…This use of "pure states" in statistical physics, as a synonym of "extremal", is distinct from pure states in quantum mechanics 8. For lattice theories in three space dimensions, non-translationally invariant equilibrium states exist below the interface roughening temperature[27][28][29]. The lower limit of four spatial dimensions…”
mentioning
confidence: 99%
“…the question whether equality of the two sets holds is discussed in [6]. A Gibbs state µ ∈ G(β) is said to be translation invariant if for any local function f : Ω → R, and any translation θ :…”
Section: Definition Of the Modelsmentioning
confidence: 99%
“…In [1] it was shown that for non-extremal Gibbs measures on Z d a Gibbs measure need not be a limiting Gibbs measure (see [1] and [2] for more details).…”
Section: Definitionsmentioning
confidence: 99%